First checklist of Tunisian sphecid wasps (Hymenoptera: Sphecidae) with new and additional records - Khedher, Hassib Ben; Yildirim, Erol; Braham, Mohamed; Ljubomirov, Toshko (Zootaxa, 2020)
The first checklist of Sphecidae of Tunisia is established. It is based on literature, on examination of Tunisian specimens present in the Muséum National d’Histoire Naturelle, Paris, France), and on specimens recently collected in Tunisia. Fifty-three species and subspecies belonging to 10 genera, 3 tribes and 4 subfamilies are listed. Three species: Parapsammophila errabunda (Kohl, 1901), Eremochares luteus (Taschenberg, 1869) and Prionyx macula (Fabricius, 1804) are recorded for the first time from Tunisia.